Surface and Mineral Changes of Primary Enamel after Laser Diode Irradiation and Application of Remineralization Agents: A Comparative In Vitro Study - Mihaela-Valentina Cîrdei; Mădălin-Marius Margan; Roxana Margan; Alexandra Ban-Cucerzan; Ion Petre; Iosif Hulka; Razvan Mihai Horhat; Darinca Carmen Todea (MDPI AG, 2024)
Objectives: The purpose of this study is to evaluate the remineralization potential of primary teeth enamel after being exposed to different laser diode therapies. Methods: Ninety-six vestibular primary teeth enamel samples were divided into eight groups (n = 12) with varying treatments: control (G1), CPP-ACP-fluoride varnish (G2), diode lasers at 980 nm (G3), 808 nm (G4), 450 nm (G5), 980 nm + CPP-ACP-fluoride varnish (G6), 808 nm + CPP-ACP-fluoride varnish (G7), and 450 nm + CPP-ACP-fluoride varnish (G8). Each sample was assessed using a DIAGNOdent® (KaVo Dental, Biberach, Germany), at baseline, post-treatment, and post-pH cycle remineralization. SEM imaging was performed before and after treatment and following the pH cycle. Results: The results indicated that the 980 nm and 808 nm diode lasers, both alone and in combination with CPP-ACP-fluoride varnish, either maintained or increased the calcium (Ca) weight percentage (Wt%) in the enamel. The 980 nm diode laser combined with CPP-ACP-fluoride varnish (G6) showed a significant increase in Ca Wt%, suggesting a strong remineralization effect. Similarly, the 808 nm diode laser alone (G4) also promoted a substantial increase in Ca Wt%. In contrast, the 450 nm diode laser, whether applied alone or in combination with CPP-ACP-fluoride varnish, resulted in a lower Ca Wt% and an increase in phosphorus (P) Wt%. Most groups, except for the CPP-ACP-fluoride varnish alone (G2), demonstrated an increase in P Wt%, indicating a complex interaction between laser therapy and enamel remineralization. Conclusions: The combined use of laser therapy with CPP-ACP-fluoride varnish significantly enhanced the remineralization of temporary teeth enamel. The 980 nm diode laser + CPP-ACP-fluoride varnish showed the most pronounced improvement in remineralization, while the 808 nm diode laser alone also effectively increased calcium solubility. These findings suggest that higher-wavelength diode lasers, particularly when combined with remineralizing agents, can effectively enhance the mineral content of primary teeth and promote enamel remineralization.